Pengaruh Mimba dan Biochar Sekam Padi terhadap Pertumbuhan Tanaman Sawi Hijau (Brassica juncea L.) - Simanjuntak, Demak Juan Brando; Kesumadewi, Anak Agung Istri; Pradnyawathi, Ni Luh Made (Agrotrop : Journal on Agriculture Science, 2025)
Effect of Neem and Rice Husk Biochar on The Growth of Green Mustard ( Brassica juncea L.). Green mustard ( Brassica Juncea L.) is one of the plants that have high economic and nutritional value. This study aims to see the interaction of neem and rice husk biochar on the agronomic efficiency of urea in green mustard plants ( Brassica juncea L.). This study used a 1-factor Randomized block design (RBD) with 10 treatments namely control, urea, rice husk biochar, neem leaves, neem seeds, Urea + rice husk biochar, urea + neem leaves, urea + neem seeds, urea + rice husk biochar + neem leaves, Urea + rice husk biochar + neem seeds. Each treatment was repeated 3 times. The research was conducted in the greenhouse Experimental Garden of the Faculty of Agriculture and Laboratory of Agronomy and Horticulture, Udayana University from June to August 2024. The addition of Urea fertilizer affects the growth and yield of green mustard plants. The treatment of Urea + Biochar rice husk + Neem seeds gave the highest results in green mustard plants, at 35 daplant height 36.67 cm, number of leaves 35 dap 13.00 strands, leaf chlorophyll content 35 dap 41.20 units, fresh weight of the top of the plant 124.33 g, fresh weight of roots 17.67 g, oven dry weight of plants above the ground 16, 29 g, root dry weight 7.02 g, whole plant fresh weight 142.00 g, whole plant oven dry weight 23.31 g, plant moisture content 108.05%compared to control 35.67 cm, 11.67 leaves, 34.20 units, 92.00 g, 10.67 g, 10.79 g, 6.68 g, 102.67 g, 17.47 g, 81.21%.